2012
DOI: 10.21608/ajesa.2012.163616
|View full text |Cite
|
Sign up to set email alerts
|

Mites Associated with the Red Palm Weevil, Rhynchophorus ferrugineus Oliver in Saudi Arabia with a Description of a New Species

Abstract: The red palm weevil (RPW) Rhynchophorus fcrrugincus Oliver is an economically important pest of palm in Al-Hassa (Eastern Province of Saudi Arabia). The RPW was noted associated with mites during May--June 2009. Three mite species were found. One of which Aegyptus alhassa n. sp. (Gamasida, Trachyuropodidae) as a parasite collected from eggs, larvae, pupae cocoons and under the elytron of insect adult was described. The second mite species Sejus sp. may feed on fungi or organic debris, while the acarid hypopial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, Hodgkin et al (2010) also found that heavily infested female hosts produced the healthiest offspring, suggesting that the effects of phoretic mites on the host may be different for adults and larvae, or that the predominant phoretic mite species changes during host life. Phoresy has been considered a precursor to parasitism, as deutonymphs of Hemisarcoptes cooremani (Thomas, 1961) have been found to parasitise their dispersal host Chilocorus cacti (Linnaeus, 1767) by using its body fluids (Houck & Cohen, 1995) Qahtani, 2012;Allam et al, 2013;Allam & Elbadawy, 2017;Allam & El-Bishlawi, 2010). Other phoretic mites are nematophagous (Kinn, 1984), which may reduce the efficacy of entomopathogenic nematodes used to treat RPW-infested palms in Portugal and other countries (DGAV, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hodgkin et al (2010) also found that heavily infested female hosts produced the healthiest offspring, suggesting that the effects of phoretic mites on the host may be different for adults and larvae, or that the predominant phoretic mite species changes during host life. Phoresy has been considered a precursor to parasitism, as deutonymphs of Hemisarcoptes cooremani (Thomas, 1961) have been found to parasitise their dispersal host Chilocorus cacti (Linnaeus, 1767) by using its body fluids (Houck & Cohen, 1995) Qahtani, 2012;Allam et al, 2013;Allam & Elbadawy, 2017;Allam & El-Bishlawi, 2010). Other phoretic mites are nematophagous (Kinn, 1984), which may reduce the efficacy of entomopathogenic nematodes used to treat RPW-infested palms in Portugal and other countries (DGAV, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous groups of mites form phoretic associations with RPW, either as specialised deutonymphs (Astigmata, Sejina, Uropodina), unspecialised deutonymphs (Digamasellidae, Parasitidae) or as adults (Heterostigmata, Trigynaspida, Dermanyssina; Abolafia & Ruiz‐Cuenca, 2020 ; Al‐Deeb et al, 2011 ; Al‐Dhafar & Al‐Qahtani, 2012 ; Allam et al, 2013 ; Dilipkumar et al, 2015 ; El‐Sharabasy, 2010 ; Farahani et al, 2016 ; Longo & Ragusa, 2006 ; Mazza et al, 2011 ; Mesbah et al, 2008 ; Porcelli et al, 2009 ; Slimane‐Kharrat & Ouali, 2019 ; Wisniewski et al, 1992 ). This form of temporary symbiotic relationship between mites (phoronts) and the weevil (host) ensures the dispersal of the former (Seeman & Walter, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the phoretic mites Aegyptus rhynchophorus Elbishlawi & Allam 2007 and Aegyptus alhassa Al-Dhafar & Al-Qahtani 2012 have been found feeding on different developmental stages of RPW and have been proposed for pest control under field conditions (Allam & El-Bishlawi, 2010;Al-Dhafar & Al-Qahtani, 2012;Allam et al, 2013;Allam & Elbadawy, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…RPW has been described to carry phoretic deutonymph mites (Astigmata, Mesostigmata) on its body (Wisniewski et al, 1992; Longo & Ragusa, 2006; Mesbah et al, 2008; Porcelli et al, 2009; El-Sharabasy, 2010; Mazza et al, 2011; Al-Deeb et al, 2011; Al-Dhafar & Al-Qahtani, 2012; Allam et al, 2013; Dilipkumar et al, 2015; Farahani et al, 2016; Slimane-Kharrat & Ouali, 2019; Abolafia & Ruiz-Cuenca, 2020). This form of temporary symbiotic relationship between mites (phoronts) and the weevil (host) ensures the dispersal of the former (Seeman & Walter, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation